Erectile function and sexual health in men with spinal cord injury : a cross sectional study (2017)
Introduction and objective The main consequences of spinal cord injury (SCI) in men are erectile dysfunction and anejaculation. The mean age of people with SCI is 35 years in Colombia, and 76% of those affected are men. Approximately 80% of men with SCI p